2019
DOI: 10.1186/s12871-019-0832-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia and avoidance of blood transfusion are associated with reduced mortality in patients with postoperative pulmonary complications following thoracotomic esophagectomy: a retrospective cohort study of 335 patients

Abstract: Background Postoperative pulmonary complications (PPCs) represent the most frequent complications after esophagectomy. The aim of this study was to identify modifiable risk factors for PPCs and 90-days mortality related to PPCs after esophagectomy in esophageal cancer patients. Methods This is a single center retrospective cohort study of 335 patients suffering from esophageal cancer who underwent esophagectomy between 1996 and 2014 at a university hospital center. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…Anesthesiology practice for cancer surgery has become increasingly complex and subspecialized . Intraoperative management, including fluid administration, invasive monitoring, transfusion thresholds, and analgesia strategies, is associated with bleeding, postoperative recovery, and potentially anastomotic healing and therefore plays an important role in optimizing outcomes . Whether and how anesthesiology case volume is associated with perioperative outcomes is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Anesthesiology practice for cancer surgery has become increasingly complex and subspecialized . Intraoperative management, including fluid administration, invasive monitoring, transfusion thresholds, and analgesia strategies, is associated with bleeding, postoperative recovery, and potentially anastomotic healing and therefore plays an important role in optimizing outcomes . Whether and how anesthesiology case volume is associated with perioperative outcomes is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Patients receiving epidural block and total intravenous anesthesia were reportedly less likely to require an unplanned admission to the intensive care unit after lung resection surgery, with a decreased duration of hospital stay and reduced mortality 13. Additionally, in patients after thoracotomic esophagectomy, epidural analgesia and the avoidance of intraoperative blood transfusion were reportedly associated with reduced mortality in relation to postoperative pulmonary complications 12. Several mechanisms that thoracic epidural analgesia spares diaphragmatic function, suppresses acute postoperative pain, and might reduce inflammatory responses after thoracic surgery, likely exerted beneficial effects on patient recovery after thoracic surgery for lung or esophageal cancer 11.…”
Section: Discussionmentioning
confidence: 99%
“…Curative-intent surgery for MPM is usually performed under general anesthesia with or without regional anesthesia, including thoracic epidural and paravertebral blocks 9. Several investigators reported that thoracic epidural block might reduce the incidence of postoperative complications after thoracic surgery for lung or esophageal cancer 10–13. Possible mechanisms of these beneficial effects of thoracic epidural block, which suppresses nociception during and after thoracic surgery, are thought to be protection of diaphragmatic function, and also reduction of acute postoperative pain and inflammatory responses 11.…”
Section: Introductionmentioning
confidence: 99%
“…As an effective treatment to correct intraoperative blood loss, blood transfusion is widely used in almost all hospitals; however, some negative effects can arise during its use, such as the spread of infectious diseases. In addition, blood transfusion also leads to some related complications[ 27 ], such as blood transfusion-related acute lung injury, blood transfusion-related graft-versus-host disease, blood transfusion-related circulatory overload, hemolytic reaction, and immunosuppression. Patients receiving blood transfusions tend to be older, have more complications, worse basic conditions, and more serious diseases.…”
Section: Discussionmentioning
confidence: 99%